The Effect of Ethanol Extract of Batak Onion (Allium Chinense G. Don.) on the Kidney Histopathology of White Rats Induced by Ethylene Glycol - Muhammad Gafra Shafa Harahap; Mhd Bayu Azhari (CV. Inara, 2025)
Ethylene glycol is a chemical compound that when entered into the body can cause damage to kidney cells/tissue. Batak onion is an ethnomedical plant that acts as a natural antioxidant that is very necessary for the body. The purpose of this study was to determine the effect of Batak onion ethanol extract on the score of kidney histopathology damage and glomerular diameter of white rats induced by ethylene glycol. This study used a completely randomized design (CRD) with 25 white rats consisting of 5 treatment groups, namely the negative control group given food and water, the positive control group 0.75% ethylene glycol, treatment group 1 0.75% ethylene glycol and ethanol extract of Batak onion 250 mg/kg BW, treatment group 2 0.75% ethylene glycol and ethanol extract of Batak onion 500 mg/kg BW, treatment group 3 0.75% ethylene glycol and ethanol extract of Batak onion 750 mg/kg BW. The research data were analyzed statistically using one-way ANOVA and Duncan's further test. The results of the study showed that the administration of Batak onion ethanol extract had an effect on the histopathological damage score of the kidneys of white rats (p<0.05) with the most optimal extract dose of 500 mg/kg BW and 750 mg/kg BW and had an effect on the glomerular diameter of the kidneys of white rats (p<0.05) with the most optimal extract dose of 500 mg/kg BW and 750 mg/kg BW. These results indicate that the administration of Batak onion ethanol extract had an effect on the histopathological damage score of the kidneys and the glomerular diameter of white rats induced by ethylene glycol.